2003
DOI: 10.1016/s0990-7440(03)00080-9
|View full text |Cite
|
Sign up to set email alerts
|

Paralytic shellfish poison accumulation yields and feeding time activity in the Pacific oyster (Crassostrea gigas) and king scallop (Pecten maximus)

Abstract: Pacific oysters and king scallops placed individually in a recirculating flume were fed for 2 weeks with a constant concentration (120 cell ml -1 ) of a toxic strain of Alexandrium minutum. Fluorescence at the outlet of each experimental unit was measured continuously, and biodeposits were recovered twice daily to evaluate feeding time activity (FTA) and rates of organic filtration (OFR), ingestion (OIR) and organic absorption (OAR). Ion-pairing high performance liquid chromatography (IP-HPLC) was performed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 14 publications
2
20
1
Order By: Relevance
“…As a filter-feeder species, C. gigas may accumulate toxins [1], [4], [5], [32] and xenobiotics [33][35]; thus toxin presence is one of the major determinants of its sanitary quality. Toxin mechanisms and effects in human and other mammalian species are widely known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a filter-feeder species, C. gigas may accumulate toxins [1], [4], [5], [32] and xenobiotics [33][35]; thus toxin presence is one of the major determinants of its sanitary quality. Toxin mechanisms and effects in human and other mammalian species are widely known.…”
Section: Discussionmentioning
confidence: 99%
“…In the first scenario, pseudo-feces production has been documented as a fundamental pre-ingestion mechanism [5], [8], [10], not only preventing exceeding the animal's ingestion capacity [10], [32], [37], [40] but also facilitating particle selection: less nutritious particles are rejected, thus the quality of ingested material is proportionally improved [5], [36], [37], [40]. However, in our work we demonstrated that the addition of a toxic dinoflagellate as G. catenatum in a diet added with the haptophyte I. galbana significantly altered C. gigas ' filtering capacity and pseudo-feces production.…”
Section: Discussionmentioning
confidence: 99%
“…In C. gigas this has been associated with their intermittent feeding pattern (i.e. periodic and non-synchronous shell closure) (Bougrier et al, 2003;Baron et al, 2006). It may also be related to genetic differences such as differential enzymatic activity, or differential prevalence of bacterial strains capable of DA degradation in the bivalve gut flora (Stewart et al, 1998;Hagström et al, 2007).…”
Section: Effect Of Body Size On Da Uptake and Eliminationmentioning
confidence: 99%
“…The experimental system used to monitor the physiological state of each oyster in the circuit is as described in several earlier publications (Bougrier et al 2001(Bougrier et al , 2003, slightly adapted for the purposes of this study. The system comprised twenty 0.5 L capacity experimental boxes, 18 containing one live oyster, and two boxes containing empty oyster shells serving as sedimentation process controls.…”
Section: Experimental Systemmentioning
confidence: 99%